1998
DOI: 10.1073/pnas.95.3.1154
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of CD4+ T cell repopulation of lymphoid tissues after treatment of HIV-1 infection

Abstract: Potent combinations of antiretroviral drugs diminish the turnover of CD4؉ T lymphocytes productively infected with HIV-1 and reduce the large pool of virions deposited in lymphoid tissue (LT). To determine to what extent suppression of viral replication and reduction in viral antigens in LT might lead correspondingly to repopulation of the immune system, we characterized CD4؉ T lymphocyte populations in LT in which we previously had quantitated viral load and turnover of infected cells before and after treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
156
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(169 citation statements)
references
References 31 publications
11
156
2
Order By: Relevance
“…Our results are consistent with a number of studies finding 2-to 6-fold higher CD4 ϩ and CD8 ϩ T cell proliferation in subjects with HIV or simian immunodeficiency virus infection (9)(10)(11)(12)(13)(15)(16)(17)(18)(19), suggesting a global activation of the immune system caused by HIV͞simian immunodeficiency virus replication. Our longitudinal studies showing declines in both fractional and absolute T cell proliferation after initiation of HAART and increases after cessation of HAART in parallel to changes in viral load clearly show that T cell proliferation is directly correlated with viral replication.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are consistent with a number of studies finding 2-to 6-fold higher CD4 ϩ and CD8 ϩ T cell proliferation in subjects with HIV or simian immunodeficiency virus infection (9)(10)(11)(12)(13)(15)(16)(17)(18)(19), suggesting a global activation of the immune system caused by HIV͞simian immunodeficiency virus replication. Our longitudinal studies showing declines in both fractional and absolute T cell proliferation after initiation of HAART and increases after cessation of HAART in parallel to changes in viral load clearly show that T cell proliferation is directly correlated with viral replication.…”
Section: Discussionsupporting
confidence: 82%
“…Studies of lymphocyte turnover derived through analysis of immediate changes in CD4 ϩ T cell counts in the blood after highly active antiretroviral therapy (HAART) also led to estimates of high rates of CD4 turnover (2)(3)(4), although others have suggested that lymphocyte redistribution may be the major cause for CD4 increases immediately after HAART (5)(6)(7)(8). Measurements of lymphocyte proliferation using Ki-67, BrdUrd, and 2 H-glucose have yielded varying results (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19); however, the general consensus is that T cell proliferation is increased in HIV͞simian immunodeficiency virus-infected subjects. Variations in these studies may be caused by the difference in sample numbers, cross-sectional versus longitudinal studies, patient cohort composition, and whether one is measuring the absolute or fractional level of cell division.…”
mentioning
confidence: 99%
“…The effects of this therapy are manifested by a strong suppression of viral replication in the peripheral blood and in lymphoid tissue in individuals infected with HIV-1 (11,12). As a result, CD4ϩT cell counts increase, T cell activation decreases, and antigen-specific and nonspecific T cell function improves (13)(14)(15)(16)(17)(18). Similarly, B cell responses are normalized, although this reversal of profound alteration of immune system is a slow and incomplete process in a number of long-term treated patients (19)(20)(21)(22).…”
mentioning
confidence: 99%
“…21,22 This is suggested by studies in patients with TCD due to HIV infection showing increased susceptibility of T cells to apoptosis with restimulation in vitro [23][24][25][26][27] and by direct labeling studies in vivo. [28][29][30] Although these observations could potentially relate to direct or indirect effects of HIV, similar results have been observed in T-cell-depleted hosts after intensive chemotherapeutic regimens 20 and after stem cell transplantation, 31 suggesting that increased susceptibility to cell death is a common phenomenon in regenerating T-cell populations. Thus, a propensity for programmed cell death in peripherally expanding T-cell populations may also limit the capacity of peripheral expansion to restore host immune competence.…”
Section: Introductionmentioning
confidence: 54%